PENGARUH PANJANG AKAR TUNGGANG DAN WAKTU SIMPAN SETELAH PENCABUTAN TERHADAP PERTUMBUHAN STUM ALBIZIA (Paraserianthes/alcataria L. Nielse) - Eko Sulistyono; Muchtar Argasasmita; , Nurharyadi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1994)
This experiment was aimed to study the effect of tap root length and storage duration on growth of Sengon stump. The field experiment was carried out as a two factors factorial experiment. The treatments were arranged in Randomized Block Design with three replications. The tap root length of 25 %, 50 %, 75 %, and 100 % of original tap root length were the levels of first factor. The storage duration 0 hours, 24 hours, 48 hours, 72 hours, and 92 hours after revoking were the levels of second factor. The tap root length affected shoot to root ratio. The least damage root gave the lowest shoot to root ratio. The root length 25 % gave the highest shoot to root ratio, but the difference between 50 %, 75 %, and 100 % were not significant. At 18 weeks after planting, the shoot diameter, shoot height, leaf number, shoot dry weight and root dry weight were not affected by tap root length and storage duration after revoking. Interaction between two factors did not effect all of the observed variables.